Dynamic Euler-Bernoulli Beam Equation: Classification and Reductions. (30th August 2015) - Naz, R.; Mahomed, F. M.
Abstract : We study a dynamic fourth-order Euler-Bernoulli partial differential equation having a constant elastic modulus and area moment of inertia, a variable lineal mass densityg ( x ), and the applied load denoted byf ( u ), a function of transverse displacementu ( t, x ) . The complete Lie group classification is obtained for different forms of the variable lineal mass densityg ( x ) and applied loadf ( u ) . The equivalence transformations are constructed to simplify the determining equations for the symmetries. The principal algebra is one-dimensional and it extends to two- and three-dimensional algebras for an arbitrary applied load, general power-law, exponential, and log type of applied loads for different forms ofg ( x ) . For the linear applied load case, we obtain an infinite-dimensional Lie algebra. We recover the Lie symmetry classification results discussed in the literature wheng ( x ) is constant with variable applied loadf ( u ) . For the general power-law and exponential case the group invariant solutions are derived. The similarity transformations reduce the fourth-order partial differential equation to a fourth-order ordinary differential equation. For the power-law applied load case a compatible initial-boundary value problem for the clamped and free end beam cases is formulated. We deduce the fourth-order ordinary differential equation with appropriate initial and boundary conditions.